Stable and Bio-Equivalent Formulation of Alginate Matrix-Based Verapamil Hydrochloride Extended-Release Tablets: Pharmaceutical Science-Industrial Pharmacy - Manohari, Packiaraj Jeyachandran; Seshadri, Venkateswaran Chidambaram; Janarthana Reddy, Narendra Reddy Parvatha; Kunchithapatham, Janakiraman; Venkatarangareddy, Harshavardhana Reddy; Chowdary Eswara Rao, Guhan Himadeep; Rao, Sumathi Vinay; Naveen Kumar, Subham Jain; Seelamantula, Srihari Teja (International Journal of Life Science and Pharma Research, 2022)
Verapamil Hydrochloride is indicated to control blood pressure in individuals due to postural and nocturnal–diurnal variations in the biological clock. The once-daily administration of Verapamil Hydrochloride is handy for patients to comply with the dosing regimen prescribed. This research aims to develop stable, bio-equivalent, cost-effective, and commercially feasible Verapamil Hydrochloride extended-release tablets, 120 mg, 180 mg and 240 mg. Inorder to achieve this aim, our objective was to explore a simple aqueous granulation involving conventional excipients viz. Sodium Alginate, Povidone, Microcrystalline Cellulose and Magnesium Stearate. The drug to polymer ratio of 1:1.35 was found to be optimum. Every unit operation involved in the process was completely optimized to achieve reproducibility and to avoid drug release variation. The designed process was scaled-up from a batch size of 75,000 tablets to 750,000 tablets. During scalability, no difference is observed in the physico-chemical characteristics of the blend or tablets. The blend and content uniformity results were found to comply with USP requirements. The manufactured product was found stable in bottle and strip packs at accelerated stability conditions for 6 months. The maximum level of the highest unknown impurity observed was 0.1% and is well within the ICH Q3BR3 requirements. Hence based on stability study results, shelf-life storage of 24 months at controlled room temperature was prescribed for the product. The end product was found to be more cost-effective (3.2 to 6.4 Indian rupees) than the brand product available nationally (within India) priced at 4.7 to 9 Indian rupees, and the physico-chemical characteristics, drug release, and stability of the manufactured drug product were comparable to the brand product available in the USA market. The similarity factor 'f2' was found to be more than 75. In the Pharmacokinetic study, the test to brand product ratio at 90% confidence interval was within 80.00-125.00%, exhibiting the developed product's bio-equivalence with the brand product. Novelty in this research is in the comprehensiveness of work done to demonstrate stability, bio-equivalence, cost-effectiveness and commercial ability aspects which were not reported elsewhere in the already published research work on Verapamil extended release tablets.